The Importance of Monitoring River Water Discharge - Depetris, P. J. (Frontiers in Water, 2021)
River discharge time series, originally recorded to anticipate floods and water scarcity, later became indispensable to design hydroelectric dams. Presently, discharge monitoring aids in detecting climatic and environmental change, because the discharge and quality of river water are functions of many climatic, biological, geological, and topographic variables coexisting in the basin. Climate change is altering the atmospheric precipitation distribution pattern -both, in time and space- as well as the occurrence of extreme climatic events. It is important to modernize the networks of river gauging stations to unveil hydrological trends and changing atmospheric patterns. Updating and expanding their original purpose, discharge monitoring stations may be invaluable in revealing the role of selected climatic/environmental variables.